Taming technology: The narrative anchor reconciling time, territory and technology in geoinformation infrastructures - Koerten, Henk (IOS, 2013)
It is often assumed that innovative technology is an essential resource for the establishment of an information infrastructure. This study on geoinformation infrastructures convincingly demonstrates that technology is an important and far more complex factor than much geoinformation practitioners want us to believe. Three Dutch cases were studied, of which two were intended to develop an infrastructure deliberately applying innovative technology. Due to a constant stream of innovations these cases failed to bring about a working infrastructure. The third case was aimed at establishing a system of large-scale basemaps. These maps acted as a ‘narrative anchor’, a non-tangible interface between innovating technology and the infrastructure to be developed. Through the narrative anchor, this infrastructure has already existed for over 35 years and is likely to continue. Its success can be attributed to the ability of the narrative anchor to reconcile different types of technology through time, both innovative and conservative. The conclusion of this book is that lasting and reliable future (geo)information infrastructures need to have a narrative anchor that will act as an interface between ever-innovating technology and infrastructure itself.